A preliminary study of hand grip strength and muscle activities - Nor Julahah Binti Jafar (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this study is to determine the strangth of the hand grip among the female and male student aged between 23-28 yearch old in malaysia. Since there is no recorded research has conducted in determine the hand grip strength with this range of age. This study participant is student from School of Manufacturing Enginearing ang School of Mechatronic, UniMAP